A low energy muon spin rotation and point contact tunneling study of niobium films prepared for superconducting cavities. (7th November 2017) - Junginger, Tobias; Calatroni, S; Sublet, A; Terenziani, G; Prokscha, T; Salman, Z; Suter, A; Proslier, T; Zasadzinski, J
Abstract: Point contact tunneling and low energy muon spin rotation are used to probe, on the same samples, the surface superconducting properties of micrometer thick niobium films deposited onto copper substrates using different sputtering techniques: diode, dc magnetron and HIPIMS. The combined results are compared to radio-frequency tests performances of RF cavities made with the same processes. Degraded surface superconducting properties are found to correlate to lower quality factors and stronger Q-slope. In addition, both techniques find evidence for surface paramagnetism on all samples and particularly on Nb films prepared by HIPIMS.